Pengembangan Model Manajemen Mutu Pendidikan Madrasah: Studi Teoritis dalam Perspektif Pendidikan Islam - Ani Apiyani (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Improving the quality of education in madrasahs is a strategic issue in enhancing the competitiveness of Islamic education in the global era. However, the implementation of quality management in madrasahs is often not yet systemically and sustainably integrated. This article aims to examine the application of Total Quality Management (TQM) in madrasah quality management and to formulate a conceptual model suited to the context of Islamic education in Indonesia. This study employs a qualitative approach using a library research method, with data collected from a range of relevant and up-to-date academic literature. The data were analyzed using content analysis to identify key concepts, theoretical relationships, and best practices in applying TQM within the madrasah environment. The findings reveal that the success of TQM implementation is influenced by transformational leadership of the madrasah principal, participation of all stakeholders, adoption of the CIPP evaluation model, and the internalization of Islamic values. This article proposes a TQM-based madrasah quality management model that is both contextual and applicable. It offers a theoretical contribution to the development of quality systems in Islamic education and recommends further field research to empirically validate the proposed model.